Copper in human health. (2nd June 2008) - Araya, Magdalena; Olivares, Manuel; Pizarro, Fernando
Copper is an essential mineral for human health and at the same time can be toxic, depending upon the amounts ingested. Copper is associated with bone health, immune function and increased frequency of infections, cardiovascular risk and alterations in cholesterol metabolism. Its metabolism is tightly intertwined with other microminerals and its deficiency is known to impair iron mobilisation, resulting in secondary iron deficiency. A pressing challenge in modern nutrition is to define both the copper dose and regimen of administration for safe human consumption; this is a difficult task because our knowledge about the limits of safe copper exposure (homeostasis), the consequences of moderate excess copper exposure and the indicators to detect early adverse effects are not well established. The article updates the knowledge of the early adverse effects derived from acute copper exposure, those associated with chronic copper exposure and discusses recent studies that explore potential indicators of early copper effects.